2007
DOI: 10.1111/j.1537-2995.2007.01408.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of pregnancies complicated by anti‐Fya alloimmunization

Abstract: Anti-Fy(a) has the potential to lead to significant fetal hemolysis. Management guidelines developed for D sensitization are appropriate for pregnancies complicated by anti-Fy(a) alloimmunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 20 publications
0
2
1
1
Order By: Relevance
“…Fy a ) have been reported to induce severe HDFN that requires intrauterine blood transfusion. This, however, rarely occurs . In our study, we observed no cases of severe HDFN in 42 antigen‐positive fetuses but phototherapy was needed in 14% of the cases, compared to 4% in controls (no antibodies present or antigen‐negative fetus) .…”
Section: Clinical Relevance Of Different Red Cell Alloantibody Specifcontrasting
confidence: 39%
“…Fy a ) have been reported to induce severe HDFN that requires intrauterine blood transfusion. This, however, rarely occurs . In our study, we observed no cases of severe HDFN in 42 antigen‐positive fetuses but phototherapy was needed in 14% of the cases, compared to 4% in controls (no antibodies present or antigen‐negative fetus) .…”
Section: Clinical Relevance Of Different Red Cell Alloantibody Specifcontrasting
confidence: 39%
“…Clinically, both antibodies against Fy a or Fy b may result in hemolytic disease of the newborn and hemolytic transfusion reactions (1,10). Moreover, several recent studies have shown that FY*A and FY*B polymorphism is associated with serum concentration of monocyte chemoattractant protein-1 (MCP-1) and affects susceptibility to Plasmodium vivax malaria (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The management of Rh-D blood type incompatible pregnancy is endorsed by the American College of Obstetricians and Gynecologists (ACOG) [2, 3]. The established treatment for prevention of sensitization during pregnancy is maternal administration of anti-D immunoglobulin [4, 5].…”
Section: Introductionmentioning
confidence: 99%